Advanced low carbon power systems - the advanced zero emissions power plant - Pagone, Emanuele (Cranfield University, 2009)
The global warming issue is becoming more and more important in the public opinion, because its effects on everyday life of the entire mankind are starting to become appreciable. On the next (2009) December will be held in Copenhagen the fifteenth United Nations Climate Change Conference which is expected to be crucial for the future choices to deal with the anthropogenic greenhouse gases issue. The power generation sector is one of the most important contributors to the emissions of greenhouse gases (of which the carbon dioxide is the main anthropogenic example), and it is facing in the last decades a problem that will exacerbate surely the already alarming effect on the global warming: the rapid increase of the world power demand. For these reasons the carbon capture topic is gaining nowadays a lot of attention, especially in the industrial sector, since it will be a strategic field for the power generation in the short-medium term. In fact, it is really likely that will be introduced soon a so-called “cap and trade” system, with the trading of pollution licences related to the CO2 emissions, as the USA president Obama has recently proposed to the Congress. This option would turn out in a completely new scenario in the power generation sector with novel, cleaner concepts being economically more attractive than the conventional ones. This project investigates the performance of a novel thermodynamic cycle with carbon capture, called Advanced Zero Emissions Power plant (AZEP), which has been analysed in the open literature just partially and superficially up to now. Since this project is part of a bigger one in which several carbon capture novel cycles options will be compared, the main objective is to provide a flexible, modular, modern computational tool, called eAZEP, developed from scratch. The second objective is the evaluation of the four main layouts of the AZEP concept as a stand alone power plant, assessing their inclination to be included in an unfired combined cycle featured with an Heat Recovery Steam Generator (HRSG). A final, third objective is the development of a routine for the off-design performance calculation to be included in on old pre-existing computational tool. The original contribution of this work to the knowledge on the topic comprises 1. the conception of two new layouts for the AZEP cycle (the Post Expan-sion Heat exchanger layouts); 2. the performance evaluation of the long term potential for the power plant; 3. a sensitivity analysis of the thermodynamic concept. The best suitable arrangements of the plant layout are identified together with the main parameters which influence their performance, both for the combined cycle perspective implementation and for the stand alone option. Thanks to the flexibility of eAZEP will be easy to consider, in a future work, a pretty wide number of alternative concepts and investigate more cycle parameters in order to broaden the conclusions obtained in this work. Moreover the combined cycle off-design new routine must be debugged and validated.